(3GdHUQ hGdHUjQI aj Yde GdYjf hYddgG heOGhJgGs - (3CHj GdMSf KGHJ Hf bQI GdMQGfj,J (B288 (3g` s ((3YHOGdQMef Hf jhfS GdEfUGQj s)
(3ChdgG (B:s
(3GdMeO ddg GdYGde HGdcjajGJ(B: (3deG cfJ SCdJ habc Gddg ddUhGH Cf CcJH dc cJGHkG aj GdYjf, CPcQ dc ajg JQcjHgG hWHbGJgG hTQM COhGJgG hfYJ CeQGVgG hCeQGV WHbGJgG hGdYdGeGJ GdOGdI Ydi LejY Pdc s
(3BNQgG (B:s
(3hLejY GdPQhGJ GdJj JbOe PcQgG, cPG jUdM Cf jchf GdCfRhJ ajgG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B384 - (3U(B451s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
GAL - (3GdLRA (B1 - (3U (B217 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B38 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH (B100) s
Keywords: (3GdWHs